2002
DOI: 10.1177/0193732502238257
|View full text |Cite
|
Sign up to set email alerts
|

“The World at their Feet”

Abstract: The global migration of footballers to and within the top professional leagues in Europe has greatly accelerated in the last decade. Commercial interests in this “football business” have also grown prodigiously and the English leagues, especially the Premier League, have experienced an associated and pronounced increase in foreign player migration. The Premier League, supported by intensive commercial investment, has placed England on the career map of some top global stars. The globalization of football and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(39 citation statements)
references
References 3 publications
1
37
0
1
Order By: Relevance
“…It is also important to consider that, as with other studies of this nature, one of the key methodological difficulties lay with access to interviewees -a problem often 520 R. Elliott exacerbated in 'the impregnable world of professional football'. 26 For this study, access was granted to the players via a gatekeeper who was a mutual acquaintance of the author and one of the players. The gatekeeper was able to gain the consent of the two other migrant players who had been based at the club in Hungary.…”
Section: Hungary For Chances: Context and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to consider that, as with other studies of this nature, one of the key methodological difficulties lay with access to interviewees -a problem often 520 R. Elliott exacerbated in 'the impregnable world of professional football'. 26 For this study, access was granted to the players via a gatekeeper who was a mutual acquaintance of the author and one of the players. The gatekeeper was able to gain the consent of the two other migrant players who had been based at the club in Hungary.…”
Section: Hungary For Chances: Context and Methodsmentioning
confidence: 99%
“…In this respect, the majority of athletic migrants gravitate towards the core, rather than away from it. 19 Migration away from the core could be explained via various factors. These might include the lack of opportunity for career development in an athlete's home nation.…”
Section: R Elliottmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the need to seek out a professional sporting experience, an intensity of commitment, the desire to test one's abilities at the highest level and the capacity to take advantage of cultural similarities such as language familiarity. 14 Additionally, Magee and Sugden 15 have shown that migration does not always occur by choice. On some occasions, players may be pushed from a particular location, they might be exiled or expelled from the league or even the country in which they currently ply their trade.…”
Section: Migration In Footballmentioning
confidence: 99%
“…Moreover, it should not be assumed that the globalisation of football and the relative (economic) success of some teams and leagues should be seen to reflect the economic success of nations in broader terms; some of the world's most powerful economies are located outside of football's economic core. 4 Given the above, it is not our intention to examine one of European football's elite leagues in this paper. Instead, we focus on what might be referred to as a transitional economy in football terms -the Polish Ekstraklasa.…”
Section: Introductionmentioning
confidence: 99%